2001
DOI: 10.1073/pnas.121178598
|View full text |Cite
|
Sign up to set email alerts
|

Total synthesis of cytochrome b562 by native chemical ligation using a removable auxiliary

Abstract: We have completed the total chemical synthesis of cytochrome b562 and an axial ligand analogue, [SeMet 7 ]cyt b562, by thioestermediated chemical ligation of unprotected peptide segments. A novel auxiliary-mediated native chemical ligation that enables peptide ligation to be applied to protein sequences lacking cysteine was used. A cleavable thiol-containing auxiliary group, 1-phenyl-2-mercaptoethyl, was added to the ␣-amino group of one peptide segment to facilitate amide bond-forming ligation. The amine-lin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
84
0
7

Year Published

2002
2002
2013
2013

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 157 publications
(92 citation statements)
references
References 37 publications
1
84
0
7
Order By: Relevance
“…7B). In contrast, previous studies showed that substitution of a methionine ligand with SeMet caused the Soret ␣ and ␤ peaks to red-shift on the range of 3-7 nm (35,36). The signals in the MCD and EPR spectra of SeMetlabeled HBD-His 6 were also unchanged from those of the native Met-containing protein (Fig.…”
Section: And Epr Spectra Reveal Spin Oxidation and Coordinationmentioning
confidence: 42%
“…7B). In contrast, previous studies showed that substitution of a methionine ligand with SeMet caused the Soret ␣ and ␤ peaks to red-shift on the range of 3-7 nm (35,36). The signals in the MCD and EPR spectra of SeMetlabeled HBD-His 6 were also unchanged from those of the native Met-containing protein (Fig.…”
Section: And Epr Spectra Reveal Spin Oxidation and Coordinationmentioning
confidence: 42%
“…Die Kentsche NCL-Strategie zur Verknüpfung einzelner Glycopeptidfragmente bençtigt einen Cysteinrest an jeder Ligationsstelle; dort werden die Peptide für die Kupplung aktiviert. Wie viele natürlich vorkommende Proteine und Glycoproteine verfügt EPO über [31] und Dawson [32] bahnbrechende Beiträge zur Entwicklung abspaltbarer Thiolbasierter Auxiliare für die NCL an cysteinfreien Stellen geleistet hatten.…”
Section: Zwei Auxiliarbasierte Ansätze Für Die Cysteinfreie Glycopeptunclassified
“…[140] Kürzlich haben Danishefsky et al das Tmb-Auxiliar in Verbindung mit einem C-terminalen Peptidphenolester 93 mit einem ortho-Disulfid (siehe Abschnitt 2.3.3) in sterisch anspruchsvollen Kupplungen zweier Glycopeptide 93 und 94, die jeweils eine N-verbrückte Chitobiose-Einheit trugen, an einer Gly-Gln-Ligationsstelle eingesetzt. [141] Hierbei wurde beobachtet, dass saure Bedingungen für die Auxiliarabspaltung zu einer Anreicherung des Thioester-Intermediats 95 durch Protonierung des sekundären Amins führen, was auf eine N!S-Verschiebung schließen lässt.…”
Section: Photospaltbare Auxiliareunclassified